The level of participation among small farmers of Sindh, Pakistan - Khushk, Ghulam Mujtaba; Abu Samah, Asnarulkhadi; Hamsan, Hanina; Ahmad, Nobaya (IDOSI Publications, 2016)
The success and failure of the projects and programs mostly rely on the level of participation of the people. Participation has been considered as a process from a development perspective through which knowledge, skills, attitudes and values are further promoted in a people oriented approach. In Pakistan, efforts have been taken towards the participation of people in various projects and programs but a few studies have been conducted to assess the level of participation in such projects and programs. Thus, the present study was attempted to assess an activity of participation in Crop Maximization Project (CMP-II) in the province of Sindh Pakistan through survey method. The general population was the small farmers and the targeted population was the beneficiaries of three districts of Sindh. The sample size was 455 at significance level of 5%. The multistage sampling method was used and responses were recorded at six points Likert Scale Questionnaire.The level of participation was divided into three dimensions namely; decision-making, implementation and benefits. The results revealed that, high level of participation was among the beneficiaries of the CMP-II based on a summated mean score of (M=178.92) and (SD=31.36). Therefore, it is concluded that the level of participation in such project has an impact on the small farmers’ communities in three districts of Sindh province, Pakistan.